Gene–obesogenic environment interactions in the UK Biobank study. (10th January 2017) - Tyrrell, Jessica; Wood, Andrew R; Ames, Ryan M; Yaghootkar, Hanieh; Beaumont, Robin N; Jones, Samuel E; Tuke, Marcus A; Ruth, Katherine S; Freathy, Rachel M; Davey Smith, George; Joost, Stéphane; Guessous, Idris; et al.
Abstract: Background: Previous studies have suggested that modern obesogenic environments accentuate the genetic risk of obesity. However, these studies have proven controversial as to which, if any, measures of the environment accentuate genetic susceptibility to high body mass index (BMI). Methods: We used up to 120 000 adults from the UK Biobank study to test the hypothesis that high-risk obesogenic environments and behaviours accentuate genetic susceptibility to obesity. We used BMI as the outcome and a 69-variant genetic risk score (GRS) for obesity and 12 measures of the obesogenic environment as exposures. These measures included Townsend deprivation index (TDI) as a measure of socio-economic position, TV watching, a 'Westernized' diet and physical activity. We performed several negative control tests, including randomly selecting groups of different average BMIs, using a simulated environment and including sun-protection use as an environment. Results: We found gene–environment interactions with TDI (Pinteraction = 3 × 10 –10 ), self-reported TV watching (Pinteraction = 7 × 10 –5 ) and self-reported physical activity (Pinteraction = 5 × 10 –6 ). Within the group of 50% living in the most relatively deprived situations, carrying 10 additional BMI-raising alleles was associated with approximately 3.8 kg extra weight in someone 1.73 m tall. In contrast, within the group of 50% living in the least deprivation, carrying 10 additional BMI-raising alleles was associated with approximately 2.9 kg extra weight. The interactions were weaker, but present, with the negative controls, including sun-protection use, indicating that residual confounding is likely. Conclusions: Our findings suggest that the obesogenic environment accentuates the risk of obesity in genetically susceptible adults. Of the factors we tested, relative social deprivation best captures the aspects of the obesogenic environment responsible.